Hybrid piezoelectric control for whirl-flutter instability - Bastos, Sérvio Túlio Suenai Haramura [UNESP]; de Vasconcellos, Rui Marcos Grombone [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The application and exploration of distinct vibration control techniques have been sought in several research with the main objective of increasing aircraft efficiency, since some aeroelastic phenomena can influence the performance and operational life, causing undesirable behaviors and failures. Considering the case of propeller-driven aircraft, the whirl-flutter is one of the phenomena that must be considered during the design of wings, nacelle, and rotors. Although nonlinearities are inherent to aeroelastic systems, their effects are usually neglected in aeroelastic analysis, thus reducing the ability to predict the realistic behavior of aircraft structural vibration. As an additional problem, some vibration control techniques cannot be applied when nonlinear behavior occurs. Therefore, considering the problems above and the importance of the whirl-flutter for the next generation of propeller-driven aircraft, the present research proposes the application of hybrid control techniques applying piezoelectrics in a rotor submitted to whirl-flutter presenting structural hardening nonlinearity. As the main result, due to the application of the active feedback control concomitantly to a passive piezoelectric controller, the stability margin of the system is significantly increased, postponing the whirl-flutter onset. Also, both the tension gain applied over the piezoelectric actuator and the external resistance applied over the piezoelectric transducer play an important role in the design of the hybrid controller since they can convert possible subcritical behavior into supercritical behavior, thus reducing the amplitudes of oscillations after the bifurcation.